2015
DOI: 10.5897/ajar2013.8434
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy in weed management: A critical review

Abstract: Allelopathy is defined as both beneficial and deleterious biochemical interaction between plant and weeds, and / or plants and microorganisms through the production of chemical compounds that escape into the environment and subsequently influence the growth and development of neighboring plants. Allelochemicals are present in all types of tissues and are released into the rhizosphere by a variety of mechanism, including decomposition of residues, volatilization and root exudation. Allelochemical its structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 91 publications
(90 reference statements)
0
5
0
2
Order By: Relevance
“…Although amaranth plants are known for high allelopathic activity (Prinsloo & Du Plooy, 2018), they are also used as a quite sensitive bioassay species to evaluate the allelopathic activity of other plants. For example, Sangeetha & Baskar (2015) reported that Helianthus annuus L., Ageratum conyzoides L., and Fagopyrum esculentum Moench strongly inhibited the growth of amaranth plants. However, in our study, we observed the opposite -aqueous extracts of S. georgicouncinata stimulated root growth of amaranth sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…Although amaranth plants are known for high allelopathic activity (Prinsloo & Du Plooy, 2018), they are also used as a quite sensitive bioassay species to evaluate the allelopathic activity of other plants. For example, Sangeetha & Baskar (2015) reported that Helianthus annuus L., Ageratum conyzoides L., and Fagopyrum esculentum Moench strongly inhibited the growth of amaranth plants. However, in our study, we observed the opposite -aqueous extracts of S. georgicouncinata stimulated root growth of amaranth sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids secreted by the roots of gramineous crops, such as corn, wheat, and rice, attract rhizobia, promoting nodulation, and nitrogen fixation in legumes. Moreover, the roots secrete momilactone B diterpenoid, benzoxazinoids, coumaric acid, and cinnamic acid, which can also inhibit weed growth, and prevent soybean phytophthora blight and watermelon fusarium wilt to coordinate the growth of surrounding plants and microorganisms (Hao et al, 2010; Li et al, 2016; Liu et al, 2017; Sangeetha & Baskar, 2015; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathy is a biological phenomenon referring to either positive and negative or direct and indirect effects of a plant species, fungi or microorganisms on other species by creating chemical compounds (allelochemicals) released into the environment (Tesio et al, 2010;Lehoczky et al, 2011;Viddotto et al, 2013). Allelochemicals which combat or remove plant species are paid special attention for their agricultural application as selective natural herbicides (Vyvyan, 2002;Sangeetha and Bashar, 2015). Ragweed generates allelochemicals which can be found in all parts of plants, and most common compounds with the allelopathic potential are terpenes and phenols (Seigler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathic effects of ragweed on other plant species should be further accounted for Buzhdygan and Baglei, 2016), although its inhibition effects on crops have been documented (Csiszár, 2009;Lehoczky et al, 2011;Sangeetha and Bashar, 2015;Bonea and sar., 2018). Vidotto et al (2013) deduced that extracts isolated from ragweed roots and leaves inhibited the growth of tomato, lettuce and wheat.…”
Section: Introductionmentioning
confidence: 99%